Duration of First-Line Antiretroviral Therapy in HIV-Infected Treatment-Naive Patients in Routine Practice. Issue 8 (November 2016) - Tesson, Thomas; Blot, Mathieu; Fillion, Aurélie; Djerad, Hama; Cagnon-Chapalain, Joséphine; Creuwels, Aline; Waldner, Anne; Duong, Michel; Buisson, Marielle; Mahy, Sophie; Chavanet, Pascal; Piroth, Lionel
Background: First-line antiretroviral therapy (1st ART) is an important step in a patient's management and often considered a long-term therapy at treatment initiation. Methods: To describe the duration of 1st ART and the factors associated with treatment modification in a recent real-life setting, antiretroviral-naive patients who began their 1st ART in six French hospitals in 2009– 2012 were included in a cohort. Clinical, immunological, virological and therapeutic data, as well as the reasons for therapeutic changes, if any, were retrospectively collected. Results: A total of 206 patients started 1st ART, mainly a protease inhibitor-based triple therapy (73%), with a tenofovir-including backbone (87%). Of these, 89 (43%) had their 1st ART modified after a median of 16.5 months (IQR 8.0–32.8). Having a CD4 + T-cell count <200 cells/mm 3, being pregnant, or 1st ART including zidovudine + lamivudine or lopinavir/r were significantly associated with a higher risk for treatment modification in multivariate analysis. In 47 patients (53%), 1st ART was modified for safety reasons, with no significant association with a given anti-retroviral drug or class. No significant difference in virological, immunological and clinical outcomes was observed between the patients who had their 1st ART modified and those who did not. Conclusions: The proportion of modifications of the 1st ART during the first 2 years remains high. These modifications are frequently because of safety issues and the willingness to simplify treatment, and less often driven by virological failure, thus emphasizing that 1st ART is not – or is no longer – a lifelong treatment.